The Cambridge companion to European novelists - Bell, Michael (Cambridge University Press, 2012)
"A lively and comprehensive account of the whole tradition of European fiction for students and teachers of comparative literature, this volume covers twenty-five of the most significant and influential novelists in Europe from Cervantes to Kundera. Each essay examines an author's use of, and contributions to, the genre and also engages an important aspect of the form, such as its relation to romance or one of its sub-genres, such as the Bildungsroman. Larger theoretical questions are introduced through specific readings of exemplary novels. Taking a broad historical and geographic view, the essays keep in mind the role the novel itself has played in the development of European national identities and in cultural history over the last four centuries. While conveying essential introductory information for new readers, these authoritative essays reflect up-to-date scholarship and also review, and sometimes challenge, conventional accounts"--